Trends and scenarios of air pollution by automotive origin in Metropolitan Lima - Zegarra Tello, Irma Janet (2021)
The transport sector plays an especially important role in the development of a country, both socially and economically. It is also highly related to climate change as it is the main producer of greenhouse gases, a situation that is not exempt for Peru, since it has a vast fleet of vehicles. For this reason, it was considered of interest to analyze the trends and possible medium-term scenarios of air pollution from automotive sources in Metropolitan Lima. The research is circumscribed in a quantitative approach, using techniques such as survey and documentary analysis. It is concluded that Metropolitan Lima is located in scenario 2, consumption of liquid fossil fuels in the process of improving its quality, with the technology EURO III and the progressive introduction of vehicles of the type EURO IV, showing lesser results over the years regarding national standards and international standards in terms of SO2 and NO2 measurement, and in terms of trends, there is a prevalence of continuing to use liquid fossil fuels.